Doctors' attitudes towards prescribing opioids for refractory dyspnoea: a single-centred study. Issue 2 (6th March 2014) - Hadjiphilippou, Savvas; Odogwu, Sarah-Elizabeth; Dand, Pauline
Abstract : Objective: Dyspnoea is a distressing and common symptom in palliative care. There is evidence that opioids can improve the experience of dyspnoea. Limited data suggest that doctors' attitudes may be a barrier to prescribing opioids for the relief of refractory dyspnoea. This study explored UK hospital doctors' experience of, and attitudes towards, prescribing opioids for refractory dyspnoea in advanced disease. Methods: Anonymous semistructured questionnaires were distributed by convenience sampling. Data were collated and descriptive analysis performed. Doctors of all grades attending routine educational events within the medical directorate of a UK district general hospital were included in this study. Results: Sixty-five questionnaires were analysed. Most doctors (61/64) reported a willingness to prescribe opioids for refractory dyspnoea, although the majority felt less confident than when prescribing opioids for pain. Three-quarters of doctors (49/65) had initiated, or under supervision, prescribed opioids for refractory dyspnoea. This was most often for a patient in the last hours/days of life (44/49), followed by patients with cancer (34/49), heart failure (26/49) and chronic obstructive pulmonary disease (COPD) (21/49). Confidence in prescribing was highest in relation to the dying and lowest in COPD. A significant proportion (40/64) of respondents expressed concerns when prescribing. Conclusions: This group of doctors was aware of the use of opioids for refractory dyspnoea and reported a willingness to prescribe opioids for this symptom. However, confidence varied considerably depending on clinical context. Fears about side effects were prevalent and should be addressed. Doctors would benefit from clearer guidance on prescribing regimes, specifically in circumstances other than the dying patient.